Passive and active muscle elasticity of medial gastrocnemius is related to performance in sprinters - Yamazaki, K.; Inoue, K.; Miyamoto, N. (European Journal of Applied Physiology, 2021)
Purpose Limited information is available on the association between muscle material properties and sprint performance. We aimed to identify whether and how the elasticity of passive and active muscle of the medial gastrocnemius (MG) is related to sprint performance.